An intact boundary between the tumor and inner hypoechoic layer discriminates T1 lesions among sessile elevated gallbladder cancers. (20th April 2021) - Toyonaga, Haruka; Hayashi, Tsuyoshi; Ueki, Hidetaro; Chikugo, Kouki; Ishii, Tatsuya; Nasuno, Hiroshi; Kin, Toshifumi; Takahashi, Kuniyuki; Takada, Minoru; Ambo, Yoshiyasu; Shinohara, Toshiya; Yamazaki, Hajime; et al.
Abstract: Background: The depth of invasion determines the surgical method for treating gallbladder cancer (GBC). However, the preoperative correct diagnosis of invasion depth, especially discrimination of T1 lesions among sessile elevated GBCs, is difficult. We investigated the utility of preoperative endoscopic ultrasound (EUS) findings for diagnosing the invasion depth. Methods: We studied a sessile elevated GBC specimen diagnosed as a T1 lesion before developing our study protocol. EUS evidenced an intact boundary between the tumor and the inner hypoechoic layer (the intact boundary sign). To evaluate the potential of using this sign to diagnose T1 GBC as a primary outcome indicator, we retrospectively analyzed patients who underwent surgical resection of sessile elevated GBCs between April 2009 and March 2020. Results: Of the 26 surgically resected sessile elevated GBC specimens, 20 were included and six were excluded due to difficulty in evaluating the overall tumor or layer structure. The Kappa coefficient for interobserver agreement regarding the intact boundary sign was 0.733. The sensitivity and specificity of the sign for diagnosing T1 lesions were 0.857 and 1.000, respectively. Conclusion: This new EUS finding could guide the accurate diagnosis of T1 lesions in patients with sessile elevated GBC. Abstract : Highlight Preoperative identification of T1 lesions among sessile elevated gallbladder cancers is difficult. Toyonaga and colleagues demonstrate that an intact boundary between a sessile elevated gallbladder cancer and the inner hypoechoic layer of the gallbladder wall without irregularity of the inner hypoechoic and outer hyperechoic layers on endoscopic ultrasound indicates a T1 lesion.